Pembangkit Listrik Tenaga Surya Off-Grid Tipe Fotovoltaik : Pengaruh Intensitas Cahaya Terhadap Output Daya, Tegangan, Dan Arus - Filian Arbiyani; William Aristo Kurniawan; Rudy Eduard; Djoko Setyanto (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2026)
As technological development advances and global population growth continues to elevateenergy demand, the persistent dependence on fossil fuels underscores the urgent need toaccelerate the deployment of renewable energy technologies. This study investigates theperformance characteristics of a photovoltaic (PV) module operating within an off-grid solarpower system (PLTS), with emphasis on quantifying the effects of solar irradiance on outputpower, voltage, and current. The experiment was conducted over a 12-hour period (06:00–18:00), during which operational parameters were recorded at one-hour intervals. The PVmodule employed is a polycrystalline unit with an effective surface area of 0.00759 m² andnominal maximum ratings of 1.1 W, 0.22 A, and 5 V. Results indicate that increases inirradiance lead to proportional increases in power output and voltage, whereas the currentremains relatively stable, exhibiting only minor variation within the 0.1–0.2 A range. Thesefindings provide insights into the irradiance-dependent behavior of small-scale off-grid PVsystems and contribute to improved performance assessment under real-world operatingconditions.